Construction of the Balanced Intellectual Capital Model in a Real Life Context. Case: Machinery Ltd. - Salmi, Katja (My University, 2003)
The primary objective of this research was to construct a Balanced Intellectual Capital Model (BICM) for a case company and to field-test the quality and usability of the information as the basis of management decision-making in practice. The purpose of the BICM is to enhance internal competencies of a company. This research is a direct continuum of Korpi’s research (2001), in which the BICM was not tested in a real life context. The second objective of this research was to explore the use and implementation of the BICM by using the institutional perspective as an explanatory factor. Since the model in question has not been field-tested before in its real purpose of use, this research provides grounds for the appraisal of the usability of the BICM in a larger extent. The third objective was to improve the BICM invented by Korpi. The research data was mainly collected by using semi-structured theme interviews, which were conducted before and after the construction of the BICM. The interviewees consisted of the top management who had a clear understanding of the corporate strategy. The interviewees also knew what kind of information is required when pursuing the company goals. The design of the case company can be considered successful since the BICM encapsulates the elements and measurements of intellectual capital which are focal to corporate strategy and competitiveness. The results of this research indicate that the statement of human resources and the BICM are not parallel to each other. The BICM provides more a profound method for measuring and controlling intellectual capital. The prior use of the statement of human resources was not found significant when constructing the BICM whereas the impact of the EFQM model (European Foundation for Quality Management) of the company was substantial. Furthermore the BICM was found genericly usable and it is applicable also in other companies and generates information which can be used to support management’s decision-making. An improved version of BICM is presented in the research findings.
Keywords: Balanced Intellectual Capital Model; constructive approach; institutional perspective; intellectual capital; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|